INVESTIGATING THE ROLE OF THE KNOWLEDGE SHARING AND INNOVATIVE BEHAVIOR IN SUPPLY CHAIN MANAGEMENT - Suhana, Suhana; Suharnomo, Suharnomo; Mas?ud, Fuad; Mansyur, Anwar; Febrianto, Boggy; Santoso, Ignatius Hari (International Journal of Supply Chain Management, 2020)
Abstract? In the era of highly competitive environment and fastly technology advance, an organization should continuously adapt and innovate. The main purpose of the research is to investigate and to analyse the effect of knowledge sharing and innovative climate  supply chain performance. The current research is also to investigate and to analyse the moderating role of the relationship between knowledge sharing and innovative behavior in supply chain management. Two hundreds and ten respondents  are the sample of the research. SPSS software was used to analyse the research data. The result showed that knowledge sharing and innovative climate significantly affected to supply chain performance. However, the study failed proving moderating role of innovative climate to the relationship between knowledge sharing and innovative behavior. Results showed to maximize knowledge sharing benefits in supply chain networks. Finally Theoritical and practical implication of the current research are conveyed.